Problematic substance use and its associated factors among street youth in Bahir Dar city, Ethiopia - Shegaw, Maregu; Fekadu, Wubalem; Beka, Michael; Menberu, Melake; Yohannes, Kalkidan; Yimer, Solomon; Seid, Mohammed; Necho, Mogesie; Moges, Solomon; Anbesaw, Tamrat (Frontiers in Psychiatry, 2022)
Background Problematic substance use is becoming a common problem in marginalized groups such as street youths. However, there is a dearth of studies on the prevalence and factors associated with problematic substance use among street youth in Ethiopia. Objective The objective of this study was to determine the prevalence of problematic substance use and identify its associated factors among street youth. Methods This community-based cross-sectional study was conducted between June and July 2020. A total of 252 participants were included in this study. Systematic random sampling was used to recruit participants. Cut down, annoyed, guilty feeling, and eye opening-adapted to include drugs (CAGE-AIDs) were used to assess problematic substance use. The data were entered into epidata and exported to SPSS version 25 for analysis. Logistic regression with a 95% confidence interval (CI) was used to show the strength of association. A p-value < 0.5 was statistically significant. Results The prevalence of problematic substance use was 55.8%, 95% CI (49–63%). Peer pressure [adjusted odds ratio (AOR) = 3.01, 95% CI: 1.38, 6.59], family conflict [AOR = 5.05, 95% CI: 1.67, 15.25], physical abuse [AOR = 2.56, 95% CI: 1.11, 5.84], and substance use in the family [AOR = 2.85, 95% CI: 1.29, 6.27] were the factors significantly associated with problematic substance use. Conclusion The prevalence of problematic substance use was high. It was also found that peer pressure, family conflict, substance use in the family, and physical abuse were the factors associated with problematic substance use. Therefore, proper screening and intervention for individuals with problematic substance use are needed, and further research should be conducted for marginalized groups.